NSAID-Induced Small Bowel Diaphragms and Strictures Diagnosed with Intraoperative Enteroscopy - Douglas A Shumaker; Kari Bladen; Ronald M Katon (Canadian Journal of Gastroenterology)
Nonsteroidal anti-inflammatory drugs are known to cause mucosal damage in the stomach and duodenum, which may lead to hemorrhage and perforation. However, these medications may also cause damage in the more distal small bowel. Due to the location of these lesions, currently available diagnostic testing may yield false negative results. Two cases of nonsteroidal anti-inflammatory drug-induced small bowel diaphragms presenting as obscure gastrointestinal hemorrhage and recurrent small bowel obstruction, respectively, are discussed. Intraoperative enteroscopy was used to confirm this diagnosis after other diagnostic tests failed to identify the etiology. This procedure may increase the accuracy of exploratory laparotomy in these challenging cases.